A human TRIM5α B30.2/SPRY domain mutant gains the ability to restrict and prematurely uncoat B-tropic murine leukemia virus - Diaz-Griffero, Felipe (2008)
Human TRIM5α restricts N-tropic murine leukemia virus (N-MLV) but not B-tropic MLV (B-MLV) infection. Here we study B30.2/SPRY domain mutants of human TRIM5α that acquire the ability to inhibit B-MLV infection prior to reverse transcription without losing the ability to restrict N-MLV infection. Remarkably, these mutants gain the ability to decrease the amount of particulate B-MLV capsids in the cytosol of infected cells. In addition, these mutants gain the ability to restrict SIV(mac) and HIV-2 infection. B-MLV and SIV(mac) infections were blocked by the mutant TRIM5α proteins prior to reverse transcription. Thus, the range of retroviruses restricted by human TRIM5α can be increased by changes in the B30.2/SPRY domain, which also result in the ability to cause premature uncoating of the restricted retroviral capsid.